MOS 2010 study guide for Microsoft® OneNote - Pierce, John (Microsoft Press, 2011)
Demonstrate your expertise with Microsoft Office! Designed to help you practice and prepare for a Microsoft Office Specialist (MOS) exam, this all-in-one study guide features:Full, objective-by-objective exam coverageEasy-to-follow procedures and illustrations to review essential skillsHands-on practice tasks to apply what you've learned; files includedOnline pre-test to assess your readinessUse the in-depth exam prep, practice, and review to help advance your proficiency with Microsoft Office--and earn the credential that proves it!Exam covered:Exam 77-853: MOS Microsoft Office OneNote 2010Com.
Includes index. - Linking Pages to Other OneNote Pages. - Print version record
Keywords: Microsoft OneNote; Computer science; Database management; Microsoft OneNote / Examinations / Study guides; Informatique; Bases de données; Gestion; COMPUTERS; Programming Languages; SQL; Education; Social Sciences; Theory & Practice of Education